Consumer perspectives on the ethics of an array of technology-based marketing strategies: An exploratory study. Issue 5 (13th November 2017) - Fullerton, Sam; Brooksbank, Roger; Neale, Larry
Abstract : Purpose: Technology-based initiatives are now being routinely incorporated within most companies' marketing strategies. The purpose of this paper is to explore consumer perspectives on the ethics of these initiatives. It also seeks to identify underlying dimensions within the technology-based strategic environment with the intent of generating advances for both academicians and practitioners alike. Design/methodology/approach: The enquiry is based on a survey featuring a cross-section of 20 technology-based initiatives. A sample of 967 adult residents of the USA provided their views of the extent to which each initiative/scenario conformed to their perception of society's norms regarding ethical acceptability. Findings: In total, 13 of the 20 initiatives were deemed unacceptable with the greatest disdain exhibited for a company posting bogus online reviews. Most acceptable were self-service checkouts. Three sub-dimensions of the ethicality construct as it relates to technology-based marketing initiatives were identified and validated as measurement scales for use in future research: involvement, communication, and privacy. Research limitations/implications: The generalization of findings may be limited because younger and older segments of the population were slightly under- and over-represented, respectively. Practical implications: Marketers should recognize that consumers are much more accepting of any initiative from which they will derive some benefit. They should also recognize that within this arena, ethical acceptability is a multi-dimensional phenomenon, necessitating that they strategize accordingly. Originality/value: Although previous research has garnered insights with respect to a particular technology-based marketing initiative, none have explored the relativities of consumer perceived ethicality across an array of different initiatives or examined any latent sub-dimensions of the construct in this arena. This study addresses these deficiencies.